Indonesians and Americans Bilingual Request Strategies in Indonesian and English - Husein, Imelda Wahyuni; Syaifullah, Aceng Ruhendi; Kurniawan, Eri (Lingua Cultura, 2024)
The research aimed to investigate the changes in the request strategies of Indonesians and Americans when they spoke English and Indonesian. In cross-cultural communication, several things needed to be considered to avoid misunderstanding, such as the addressee’s knowledge, experience, culture, and value. Different kinds of request strategies in intercultural communication between Indonesians and Americans could lead to misunderstanding. The research applied a qualitative research involving five Indonesian and American speakers who speak English and Indonesian fluently. The data were collected through multiple resources such as the Discourse Completion Test (DCT) with certain situations, which was distributed to the participants, and observation and interview during the meeting with the participants. The findings show that Indonesians tend to be more direct when they make requests in Indonesian, while they change into indirect request strategies when making requests in English, while American participants tend to be indirect when making requests in English even though some of them are direct and changing into direct strategies when making a request in Indonesian. It also reveals that Indonesians tend to be more direct than Americans when they use their native language. It contradicts other studies that say Indonesians tend to use indirect requests, which also influences Americans in how they make requests in Indonesia. Therefore, it is suggested that intercultural knowledge is important in language learning to avoid misunderstanding due to the differences in norms, values, and beliefs.